Coat-of-arms of BMC - Ghosh, Ayan (Jio Institute, 2023)
The coat-of-arms of the Brihanmumbai Mahanagarpalika (Municipal Corporation of Greater Mumbai) is prominently displayed on the facade of the BMC building. It is a four-panel shield surmounted by a heraldic lion and a blooming lotus at the base. The Sanskrit motto यतो धर्मस्ततो जय: Yato Dharmas Tato Jayaḥ (Where there is Righteousness, there shall be Victory) is inscribed in gold at the bottom.